Factors affecting the use of modern contraception among women of reproductive age in Odigbo local government area, Ondo state, Nigeria - Adeniji, Oluwakemi I.; Adeniji, Adetunji O. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Modern contraception, one of the components of reproductive health, and an essential one for that matter, affects the health of women positively. It consists of modern contraceptive methods which are of different products or medical procedure that inhibits pregnancy following sexual intercourse. The study assessed the factors affecting the use of modern contraception among women of reproductive age in Odigbo local government area (LGA), Ondo State, Nigeria. Methods: A cross sectional descriptive research design was adopted for the study and the study population were women of child-bearing age between the ages of 19-45 years. A formula was used to calculate the sample size, with 420 derived, and a simple random sampling was used to select the respondents. A semi-structured instrument with its reliability tested by test re-test was used for collection of data from the respondents. The data collected was analyzed using frequency and percentage presented in tables. Results: The study revealed a mean age of 27±1.1. Also, it revealed good knowledge (90%) and practices (65.7%) as well as positive attitude (75%) towards the use of modern contraceptives among the respondents, but these were hindered by lack of support from spouses (27.4%), belief that it promotes promiscuity (29.5%), causes infertility (22.4%) and infection (46.2%). Conclusions: Based on these findings, there is need for male involvement in family planning matters and health education on modern contraceptives.